PERANAN KINERJA OPERATOR TERHADAP KELANCARAN KEGIATAN BONGKAR MUAT PERUSAHAAN FREIGHT FORWARDING - Haris Haris; Yosua Raka Sakti; Duyesna Perawati (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The aim of this research is to find out the loading and unloading operator performance on the effectiveness of container loading and unloading operator at PT. Sarana Bandar Nasional Jakarta.  The process of loading and unloading normally needs supporting equipments.  These supporting equipments generally divided into two kinds: mechanical and non-mechanical. The mechanical equipment owned by PT. Sarana Bandar Nasional are Forklift, Truck Trailer, Reach Taker, and Ship Gear (Ship Crane). In addition, the non-mechanical equipment owned are Wire Sling, Hook, Spider, and Net. These two kinds of equipments need their own operators.  One way to overcome the obstacles is by giving out workshops, so that the operators would understand theoretically on how to operate the mechanical equipments righteously.  Using the equipment in a correct way, would accelerate the duration of loading and unloading activities, besides, by using the equipment in accordance to the procedure will affect the durability of the equipment.